Labor Demand Responses to Changing Gas Prices - Mario Bossler; Alexander Moog; Thorsten Schank (Institute of Labor Economics (IZA), 2023)
In course of the current energy crisis, the consequences of increasing gas prices are heavily discussed. To date, however, there is no evidence of the impact of gas prices on the labor market. Using administrative employment data from 2012–2020, we find for manufacturing establishments a gas price elasticity of labor demand of -0.02, likely reflecting a scale effect. We also show that a rise in the gas price leads to an increase in establishment closure. A negative impact of the gas price on wages of 2 percent is consistent with rent-sharing.
Keywords: J23; Q31; 330; labor demand; gas price; elasticity; wages; establishment closure